Characterization and Manipulation of the Pathway-Specific Late Regulator AlpW Reveals Streptomyces ambofaciens as a New Producer of Kinamycins - Bunet, Robert (American Society for Microbiology (ASM), 2011)
The genome sequence of Streptomyces ambofaciens, a species known to produce the congocidine and spiramycin antibiotics, has revealed the presence of numerous gene clusters predicted to be involved in the biosynthesis of secondary metabolites. Among them, the type II polyketide synthase-encoding alp cluster was shown to be responsible for the biosynthesis of a compound with antibacterial activity. Here, by means of a deregulation approach, we gained access to workable amounts of the antibiotics for structure elucidation. These compounds, previously designated as alpomycin, were shown to be known members of kinamycin family of antibiotics. Indeed, a mutant lacking AlpW, a member of the TetR regulator family, was shown to constitutively produce kinamycins. Comparative transcriptional analyses showed that expression of alpV, the essential regulator gene required for activation of the biosynthetic genes, is strongly maintained during the stationary growth phase in the alpW mutant, a stage at which alpV transcripts and thereby transcripts of the biosynthetic genes normally drop off. Recombinant AlpW displayed DNA binding activity toward specific motifs in the promoter region of its own gene and that of alpV and alpZ. These recognition sequences are also targets for AlpZ, the γ-butyrolactone-like receptor involved in the regulation of the alp cluster. However, unlike that of AlpZ, the AlpW DNA-binding ability seemed to be insensitive to the signaling molecules controlling antibiotic biosynthesis. Together, the results presented in this study reveal S. ambofaciens to be a new producer of kinamycins and AlpW to be a key late repressor of the cellular control of kinamycin biosynthesis.